Psychological co-morbidities of physical illness a behavioral medicine perspective - Pagoto, Sherry; SpringerLink (Online service). (New York Springer, 2011)
The scenario is all too common, patients presenting with medical conditions who have co-occurring psychological disorders, and vice versa. Clinical challenges include poor treatment outcome, low adherence, and impaired quality of life. Yet as a common clinical phenomenon, these co-morbidities tend to be understudied by researchers and undertreated by practitioners. Psychological Co-Morbidities of Physical Illness is the first comprehensive reference addressing the topic from a behavioral medicine perspective and focusing on evidence-based practice. This accessible volume explains the physiological and behavioral mechanisms underlying co-morbid physical and psychological disorders, addresses treatment approaches and challenges with this population, and synthesizes findings across the disciplines. Each chapter focuses on a chronic medical condition and the most prevalent co-morbid psychological disorders for each, such as depression, anxiety, and psychotic disorders. For each condition, contributors review the treatment outcome literature and provide detailed information about effective psychological and pharmacological interventions, assessment instruments, treatment considerations (e.g., sequencing, contraindications), and, where relevant, cultural issues. Among the medical conditions covered:Obesity Type 2 diabetes Cardiovascular disease Tobacco dependence Chronic pain CancerDementia Chronic obstructive pulmonary disease Irritable bowel syndrome Multiple sclerosis Psychological Co-Morbidities of Physical Illness is an invaluable decision-making resource for practitioners and trainees working with co-morbid patients in clinical, public health, and academic settings, including psychologists and other mental health professionals, primary care and specialist physicians, nurses, and allied health care providers. Researchers and epidemiologists will find it a highly useful source of current data as well as a springboard for future research.
Psychological Co-morbidities of Obesity -- Psychological Issues in Adults with Type 2 Diabetes -- Psychological Co-morbidities of Cardiovascular Disease -- Psychological Co-morbidities of Cancer -- Tobacco Addiction and Psychological Co-morbidities -- Psychological Co-morbidities of HIV/AIDS -- Psychological Co-morbidities in Patients with Pain -- Psychiatric Disorders, Stress, and Their Treatment Among People with Multiple Sclerosis -- Psychological Co-morbidities of Dementia -- Psychological Co-morbidities of Irritable Bowel Syndrome -- Psychological Co-morbidities of COPD.
Electronic reproduction.
Keywords: Comorbidity; Medicine and psychology; Electronic books